P216 Evaluating a motivational interviewing clinic for behaviour change. (8th June 2017) - Grundy-Bowers, Matthew; Dosekun, Olamide; Osborn, Nick
Abstract : Introduction: A service was set up to support patients in behaviour change, staffed by motivational interviewing trained nurses and workers from a voluntary drugs service. Methods: An evaluation was undertaken of the service. Between 16.09.15 and 09.11.16 at total of 101 patients were booked into the service: 53 were referred to the nurses and 48 referred to the drug worker (some were referred to both). A total of 30 patient notes were selected at random and data extracted. Results: Of the 101 patients 4 were female and 97 were male (aged 21 to 63 years old). 3 were bisexual, 5 heterosexual, the remainder MSM and 5 were sex workers. Of the 12 HIV-positive patients, all were on treatment and undetectable. In the 12-months prior to referral 15 had been diagnosed with at least 1 STI and 8 had received PEPSE (2 receiving 2 courses). Reasons for attendance; chemsex (20), substance use (7), alcohol (1) risky sexual (1) not documented (1). 19 patients had been seen within 3 attendances (range 1 to 11) and the majority did not require onward referral (n=21). Discussion: There was a high DNA rate within the service which is common among this patient type. 8 patients reduced or stopped the behaviour that they were referred for. 9 of the 15 diagnosed with an STI prior to referral did not have an STI documented in their notes post referral. This shows that MI based programmes have utility in supporting vulnerable patients desiring behaviour change.